Digitalization of Government Services and Citizen Satisfaction: A Case Study in Dhankuta District, Nepal - Phuyal, Pradeep (Prashasan: The Nepalese Journal of Public Administration, 2024)
This study, conducted in the context of Nepal's Digital Nepal initiative, is of significant relevance as it evaluates citizen satisfaction with digital government services in Dhankuta District. The findings, crucial for the ongoing digital transformation in Nepal, reveal mixed satisfaction: digital services like land map printing and online revenue payments scored medium-high, indicating positive reception. However, service quality, data security, and digital awareness campaigns scored medium-low, highlighting areas for improvement. The study underscores the importance of enhancing service reliability, security, and public awareness as digital initiatives progress. Recommendations include improving user interfaces, implementing robust security measures, launching comprehensive digital literacy programs, and developing effective communication strategies to optimize digital government services in Dhankuta District.